PREVALENCE OF DEPRESSION AND ANXIETY AMONG UNDERGRADUATE MEDICAL STUDENTS IN A GOVERNMENT MEDICAL COLLEGE OF KARACHI - Deepak, Pooja; Usmani, Urooj Un Nisa; Washdev, Washdev; Mirza, Daniyal; Naz, farah; Das, Kheenpal; Rehman, Raza Ur (Journal of Postgraduate Medical Institute, 2017)
Objective: To determine the prevalence of depression and anxiety (PDA) among undergraduate medical students including both males and females studying in a public university and to see whether an association exists between the academic year of study and the PDA. Methodology: A cross-sectional study, using a self-administered, structured, validated questionnaire, was conducted on a total of 325 medical students selected through convenience sampling technique at Dow Medical College. An english version of the AGA KHAN UNIVERSITY ANXIETY AND DEPRESSION SCALE (AKUADS) was used for evaluating the prevalence of depression and anxiety with inclusion of basic personal information of the students. Results: With a 100% response rate and a cutoff score of 20, 36.3% (118 out of 325) of the sampled population was found to be at risk of anxiety and depression. There was no significant association of depression and anxiety with gender and academic year of study but there was a significant association of depression and anxiety with positive family history. Conclusion: Medical students in university of Karachi are at risk of depression and anxiety with positive family history acting as an add-on factor.